The Impact of Engagement, Work-Life Balance, and Training on Employee Turnover with Compensation as a Mediator - Siti Romiyatun; Sri Lestari Prasilowati (Yayasan Amerta Insan Unggul, 2024)
The high rate of employee turnover remains one of the critical challenges in human resource management, particularly in maintaining the stability and sustainability of company operations. Internal factors such as employee engagement, work-life balance, and training effectiveness are believed to influence turnover. Conversely, compensation is considered a key factor that may mediate the relationship between these variables and employees’ decisions to remain in or leave the organization. This study aims to analyze the effects of employee engagement, work-life balance, and training effectiveness on employee turnover, with compensation acting as an intervening variable at PT Maju Bersama Trussco. Employing a quantitative approach, the study used a survey method by distributing questionnaires to 100 respondents. The sampling technique applied was purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach via SmartPLS software. The analytical procedures included outer model testing, inner model testing, and hypothesis testing to examine both direct and indirect effects among variables. The findings reveal that employee engagement, work-life balance, and training effectiveness have a positive and significant impact on employee turnover. This suggests that higher levels of engagement, better work-life balance, and more effective training are associated with a greater likelihood of employees leaving the company. Additionally, all three independent variables were found to have a positive and significant effect on compensation. While compensation also positively and significantly affects turnover, it does not function as a mediating variable in the relationships between employee engagement, work-life balance, and training effectiveness with turnover.